Pengenalan Literasi Dasar Pada Anak Usia Dini Dengan Mengggunakan Kartu Belanja - Muhammad Hamdani (Jurnal CARE (Children Advisory Research and Education), 2023)
The purpose of this study was to determine the increase in early childhood literacy by using Shopping Cards. The method used in this study is by using a case study. Data analysis techniques using observation, interviews and documentation. Based on research data, the use of shopping cards in an effort to stimulate basic literacy skills in early childhood can increase children's basic literacy. The concept of its use applies the use of a foreign language, namely English. As well as the concept of collecting ten pieces of garbage as the child's responsibility for snacks or food consumed on that day.